Characterizing and Mitigating Cyanobacterial Blooms in Drinking Water Reservoirs. Issue 4 (3rd May 2022) - Adams, Hunter; Smith, Stephanie A.; Reeder, Sam; Appleton, Emily; Leinweber, Butch; Forbes, Steve; Barrowman, Polly; Ford, Greg; Ikehata, Keisuke; Southard, Mark
Key Takeaways: Successful detection and treatment of cyanobacterial blooms benefit from a thorough understanding of them. The sooner a harmful algal bloom is detected and identified, the easier and less expensive it will be to eliminate it. Many tools are available to refine monitoring and mitigation methods; research and technological advances continue to help support water utilities' efforts. A laboratory in Wichita Falls, Texas, has developed a proactive, multifaceted approach to address the complexities of monitoring and mitigating blooms.